#TITLE_ALTERNATIVE# - SURYA (NIM : 12211035), ABDI
Coal Bed Methane (CBM) is one type of unconventional energy are continuously being developed as alternative energy to meet domestic energy needs in some countries in the world, including Indonesia. Unlike conventional energy resources such as oil and gas, producing gas from CBM reservoir takes time to produce large amounts of water before the gas can be produced at a relatively more stable flow rate. This process is called Dewatering Time. Basically, long dewatering time is an undesirable phase because it takes a significant time, so that from economy aspect, it will hinder the economic gains for both company and government. This study focused on the development of production wells pattern to shorten the dewatering time of thick and low-down dip CBM reservoir by using CMG-GEM Simulator Software. Studies will be performed in some cases, including horizontal wells pattern, directional wells pattern, and vertical wells pattern. Prior to that, in this study will be also performed the sensitivity of CBM reservoirÃ‚Â’s dip to the production profile which are divided into three cases, including 0, 10, and 20 degrees. Furthermore, there will be performed analyze of the production wells pattern which show the production profile with the shortest dewatering time of thick and low-down dip CBM reservoir. At the end of this paper, there will be performed the sensitivity of interval activation time from three directional well to the production profile of thick and low-down dip CBM reservoir